Synthesis, Characterization and Bioactivity Study of Cobalt(III) and Ruthenium(III) Complexes of 4,4'-Cyclohexylidene Bisphenol - Jayamani, V.; Kalpana, P. (Asian Journal of Chemistry, 2011)
Co(III) and Ru(III) complexes of 4,4'-cyclohexylidene bisphenol were synthesized and characterized by physical data, elemental analysis, molar conductance, IR, UV-VIS and TGA studies. Both the ligand and complexes were screened against Staphylococcus aureus and Candida albicans. They showed little activity when compared to standard drug chloramphenicol.